[Rezension von: Robyn Faith Walsh, The origins of early Christian literature] - Becker, Matthias (de Gruyter, 2022)
Robyn Faith Walsh, The origins of early Christian literature. Contextualizing the New Testament within Greco-Roman literary culture, Cambridge - New York (Cambridge University Press) 2021, XIX, 225 S., ISBN 978-1-108-83530-5 (geb.), £ 75,–
In: Klio, 104 (2022), Nr. 1. pp. 406-410. ISSN 0075-6334 (Druck-Ausg.); 2192-7669 (Online-Aug.)